A PET/MR Imaging Approach for the Integrated Assessment of Chemotherapy-induced Brain, Heart, and Bone Injuries in Pediatric Cancer Survivors: A Pilot Study - Theruvath, Ashok J.; Ilivitzki, Anat; Muehe, Anne; Theruvath, Johanna; Gulaka, Praveen; Kim, Christine; Luna-Fineman, Sandra; Sakamoto, Kathleen M.; Yeom, Kristen W.; Yang, Phillip; Moseley, Michael; Chan, Frandics; et al. (Radiology, 2017)
Purpose To develop a positron emission tomography (PET)/magnetic resonance (MR) imaging protocol for evaluation of the brain, heart, and joints of pediatric cancer survivors for chemotherapy-induced injuries in one session. Materials and Methods Three teams of experts in neuroimaging, cardiac imaging, and bone imaging were tasked to develop a 20-30-minute PET/MR imaging protocol for detection of chemotherapy-induced tissue injuries of the brain, heart, and bone. In an institutional review board-approved, HIPAA-compliant, prospective study from April to July 2016, 10 pediatric cancer survivors who completed chemotherapy underwent imaging of the brain, heart, and bone with a 3-T PET/MR imager. Cumulative chemotherapy doses and clinical symptoms were correlated with the severity of MR imaging abnormalities by using linear regression analyses. MR imaging measures of brain perfusion and metabolism were compared among eight patients who were treated with methotrexate and eight untreated age-matched control subjects by using Wilcoxon rank-sum tests. Results Combined brain, heart, and bone examinations were completed within 90 minutes. Eight of 10 cancer survivors had abnormal findings on brain, heart, and bone images, including six patients with and two patients without clinical symptoms. Cumulative chemotherapy doses correlated significantly with MR imaging measures of left ventricular ejection fraction and end-systolic volume, but not with the severity of brain or bone abnormalities. Methotrexate-treated cancer survivors had significantly lower cerebral blood flow and metabolic activity in key brain areas compared with control subjects. Conclusion The feasibility of a single examination for assessment of chemotherapy-induced injuries of the brain, heart, and joints was shown. Earlier detection of tissue injuries may enable initiation of timely interventions and help to preserve long-term health of pediatric cancer survivors. RSNA, 2017 Online supplemental material is available for this article.